Breaking the Barriers of a "Silenced Identity": Teacher Trainees' Attitudes towards the Bilingual Presentation in Hebrew and Amharic - Baratz Lea (Journal of Education and Learning (EduLearn), 2015)
The current study investigated the attitudes of students in a teacher training college training regarding the bilingual presentation of children's literature -- in Hebrew and Amharic. A questionnaire on the importance of bilingual books was used with a group of students of Ethiopian descent (of the Beta Israel community) and a group of students who do not belong to this community, with the expectation that a substantial difference would be found between the attitudes of the two groups. The study population, students training to be literature teachers, was aware of the qualities that make "a good story". The main findings emphasize that participants have a substantial understanding of the significance of bilingual books, both in terms of its function in the curriculum and in building a cultural narrative in order to break out of the silenced identity and eliminate cultural visibility.